A Krüppel-like factor establishes cellular heterogeneity during schistosome tegumental maintenance. - Lu Zhao; George R Wendt; James J Collins Iii (PLoS Pathogens)
Schistosomes are blood dwelling parasitic flatworms that can survive in the circulation of their human hosts for decades. These parasites possess a unique syncytial skin-like surface tissue known as the tegument that is thought to be uniquely adapted for survival in the blood by mediating evasion of host defenses. Previous studies have shown that cell bodies within the tegumental syncytium are turned over and perpetually replaced by new tegumental cells derived from a pool of somatic stem cells called neoblasts. Thus, neoblast-driven tegumental homeostasis has been suggested to be a key part of the parasite's strategy for long-term survival in the blood. However, the comprehensive set of molecular programs that control the specification of tegumental cells are not defined. To better understand these programs, we characterized a homolog of a Krüppel-like factor 4 (klf4) transcription factor that was identified in previous single-cell RNA sequencing (scRNAseq) studies to be expressed in a putative tegument related lineage (TRL) of Schistosoma mansoni. Here, using a combination of RNAi, coupled with scRNAseq and bulk RNAseq approaches, we show that klf4 is essential for the maintenance of an entire TRL. Loss of this klf4+ TRL resulted in loss of a subpopulation of molecularly unique tegument cells, without altering the total number of mature tegumental cells. Thus, klf4 is critical for regulating the balance between different cell populations within the tegumental progenitor pool and thereby influences tegumental production dynamics and the fine-tuning of the molecular identity of the mature tegument. Understanding the functions of distinct populations of cells within the tegumental syncytium is expected to provide insights into parasite defense mechanisms and new avenues for combatting the disease these worms cause.